2007
DOI: 10.1534/genetics.107.075960
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Background Modifies Inner Ear and Eye Phenotypes of Jag1 Heterozygous Mice

Abstract: Mice heterozygous for missense mutations of the Notch ligand Jagged1 ( Jag1) exhibit head-shaking behavior indicative of an inner ear vestibular defect. In contrast, mice heterozygous for a targeted deletion of the Jag1 gene ( Jag1 del1 ) do not demonstrate obvious head-shaking behavior. To determine whether the differences in inner ear phenotypes were due to the types of Jag1 mutations or to differences in genetic background, we crossed Jag1 del1 heterozygous mice onto the same genetic background as the misse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…The Jag1 ligand is also expressed in the cochlear duct as the first hair cells differentiate (Figure 1C), and later in supporting cells (Morrison et al, 1999; Woods et al, 2004). Jag1 heterozygous mice also have increased inner hair cells (Kiernan et al, 2007; Moayedi et al, 2014), and we observed a similar phenotype of duplication of inner hair cells and inner phalangeal cells in Jag1 heterozygous mice (Figure 3A,B). We also confirmed that loss of both Lfng and Mfng led to a reduction in Notch signaling directly, by comparing N1ICD staining in Lfng;Mfng embryos to wild type controls (Figure 4A).…”
Section: Resultssupporting
confidence: 75%
“…The Jag1 ligand is also expressed in the cochlear duct as the first hair cells differentiate (Figure 1C), and later in supporting cells (Morrison et al, 1999; Woods et al, 2004). Jag1 heterozygous mice also have increased inner hair cells (Kiernan et al, 2007; Moayedi et al, 2014), and we observed a similar phenotype of duplication of inner hair cells and inner phalangeal cells in Jag1 heterozygous mice (Figure 3A,B). We also confirmed that loss of both Lfng and Mfng led to a reduction in Notch signaling directly, by comparing N1ICD staining in Lfng;Mfng embryos to wild type controls (Figure 4A).…”
Section: Resultssupporting
confidence: 75%
“…Interestingly, similar to other Jag1 phenotypes (Kiernan et al, 2007), the biliary phenotype is highly background dependent, as backcrossing of Jag1 +/− into a C57BL/6J background results in defects similar to those observed in Jag1/Notch2 double heterozygotes (Thakurdas et al, 2016). This study also revealed that Jag1 stability is negatively regulated by O-glucosyltransferase 1 (POGLUT1, also known as Rumi), and that reduced Rumi levels in Jag1 +/− /Rumi +/− animals rescue the biliary phenotype of Jag1-deficient animals.…”
Section: Notch2 and Jag1 Function In The Liversupporting
confidence: 82%
“…The Jag2 sm phenotype is recessive and homozygous lethal in several pups after birth. Interestingly, Hans Grüneberg observed that several phenotypes are dependent on genetic background, which, as mentioned previously, is also the case for Jag1 (Kiernan et al, 2007). Furthermore, sm/sm mice often have twisted or kinked tails, which can be indicative of neural tube defects, although in this case appears to be related to epidermal hyperplasia.…”
Section: Insights From 'Big Data' Analysesmentioning
confidence: 52%
See 1 more Smart Citation
“…Most of these compound mutants (10/14) exhibited semicircular canal truncations, but neither Sfswap Tg/Tg nor Jag1 +/− mutants have canal truncations on this genetic background (Figure 6A). Jag1 +/− mutants are known to have variations in semicircular canal defects depending on the genetic background [33]. To test if this is the case for the FVB/N background on which our Sfswap Tg mice were maintained, Jag1 +/− mice were crossed one and two generations to wild-type FVB/N mice.…”
Section: Resultsmentioning
confidence: 99%